Online water quality monitoring: a case study in the umbulan drinking water supply system, East Java, Indonesia - Rahim, Jusman; Sunarsih, Sunarsih; Budiati, Lilin (International Journal of Public Health Science (IJPHS), 2024)
Conventional systems that monitor the supply system periodically are considered to be very inadequate. This can cause the water supply distributed to the community to be of poor quality. Therefore, this study aims to evaluate water quality periodically by measuring water parameters such as pH, chlorine and turbidity for 30 days using an online system and portable unit. Portable tools used to measure pH, turbidity and residual chlorine are as follows, namely pH meters (Hanna, HI98017), Turbidity Meters (Hanna, HI 98703), Residual Chlorine meters and measurements with an online system using "Supervisory Control and Data Acquisition”. The average parameter value of the results of online daily monitoring for a month for the pH parameter was a minimum 6.92, a maximum of 7.46, a minimum turbidity of 0.08 nephelometric turbidity unit (NTU) and a maximum of 0.94 NTU. While the residual chlorine minimum of 0.29 mg/L and a maximum of 0.58 mg/L. To determine the accuracy of the offline measurements, measurements were also performed with a portable device four times a month. The comparison of the measurement results is very small, which is the difference in pH parameters is between 0.37-0.50, turbidity is between 0.05-0.21 NTU, and residual chlorine is 0.002-0.006 mg/L. Offline measurements using the portable device are consistent with the online daily monitoring. Future research should focus on optimizing sensor technology for enhanced accuracy and reliability, and developing automated data analysis algorithms to streamline evaluation processes.